Response of bats to light with different spectra: light-shy and agile bat presence is affected by white and green, but not red light. Issue 1855 (31st May 2017) - Spoelstra, Kamiel; van Grunsven, Roy H. A.; Ramakers, Jip J. C.; Ferguson, Kim B.; Raap, Thomas; Donners, Maurice; Veenendaal, Elmar M.; Visser, Marcel E.
Abstract : Artificial light at night has shown a remarkable increase over the past decades. Effects are reported for many species groups, and include changes in presence, behaviour, physiology and life-history traits. Among these, bats are strongly affected, and how bat species react to light is likely to vary with light colour. Different spectra may therefore be applied to reduce negative impacts. We used a unique set-up of eight field sites to study the response of bats to three different experimental light spectra in an otherwise dark and undisturbed natural habitat. We measured activity of three bat species groups around transects with light posts emitting white, green and red light with an intensity commonly used to illuminate countryside roads. The results reveal a strong and spectrum-dependent response for the slow-flying Myotis and Plecotus and more agile Pipistrellus species, but not for Nyctalus and Eptesicus species. Plecotus and Myotis species avoided white and green light, but were equally abundant in red light and darkness. The agile, opportunistically feeding Pipistrellus species were significantly more abundant around white and green light, most likely because of accumulation of insects, but equally abundant in red illuminated transects compared to dark control. Forest-dwelling Myotis and Plecotus species and more synanthropic Pipistrellus species are thus least disturbed by red light. Hence, in order to limit the negative impact of light at night on bats, white and green light should be avoided in or close to natural habitat, but red lights may be used if illumination is needed.